Recurrent Objections to the Minimax Strategy - Koo, Anthony Y. C. (The Review of Economics and Statistics, 1959)
T HE minimax strategy is the foundation of the theory of games of von Neumann and Morgenstern. It may sound surprising that after a decade of discussion, objections based on certain misconceptions still prevail in the professional literature. Although one may take comfort in the thought that the impact of most theoretical development, such as that of modern physics, is often not appreciated till after decades, yet such persistent misunderstanding of this basic theorem should certainly be dispelled. Three papers deserve particular attention because they encompass a broad range of common criticisms. papers are: Hans Neisser, The Strategy of Expecting the Worst '; Carl Kaysen, The Minimax Rule of the of Games and the Choices of Strategies under Conditions of Uncertainty2; and Daniel Ellsberg, Theory of Reluctant Duelist. 3 To avoid repetition, I shall single out only certain aspects of each paper to illustrate my point, since some of the remarks can be directed to the others as well.